2019
DOI: 10.1007/s10571-019-00667-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Selected Antioxidant Agents in Preventing Cisplatin-Induced Damage of Human Neurons In Vitro

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a side effect of platinum-based chemotherapy and decreases the quality of life of cancer patients. We compared neuroprotective properties of several agents using an in vitro model of terminally differentiated human cells NT2-N derived from cell line NT2/D1. Sodium azide and an active metabolite of amifostine (WR1065) increase cell viability in simultaneous treatment with cisplatin. In addition, WR1065 protects the non-dividing neurons by decreasing cisplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Amifostine was also tested for prevention of CIPN, because one of its active metabolites, WR1065, has been demonstrated to protect differentiated neurons from cisplatin-induced damage [ 98 ]. This thiol accumulates in normal tissues more than in tumors, protecting them from side effects of radiation and chemotherapy without decreasing their therapeutic efficacy [ 177 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amifostine was also tested for prevention of CIPN, because one of its active metabolites, WR1065, has been demonstrated to protect differentiated neurons from cisplatin-induced damage [ 98 ]. This thiol accumulates in normal tissues more than in tumors, protecting them from side effects of radiation and chemotherapy without decreasing their therapeutic efficacy [ 177 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown, patients treated with chemotherapy have a lower capacity for anti-oxidant ( 22 , 23 ). Therefore, it is assumed using some material such as ginseng and its derivatives, which have anti-oxidant properties can reduce the production of free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…CSP kills the tumor cells through activation or inhibition of several molecular pathways, including excessive production of reactive oxygen species (ROS) and overload entry of Ca 2+ (Nazıroğlu and Braidy 2017;Xie et al, 2018). However, there is adverse effect CSP in neurons through the imbalance between CSP and excessive oxidative stressinduced overload calcium ion (Ca 2+ ) entry, although the adverse effects of CSP were treated by antioxidants (Piccolini et al 2013;Chen et al 2019;Popović et al 2019).…”
Section: Introductionmentioning
confidence: 99%